Embedded Software for SoC - Jerraya, Ahmed Amine; Sungjoo Yoo; Wehn, Norbert; Verkest, Diederik (Springer US, 2003)
The evolution of electronic systems is pushing traditional silicon designers into areas that require new domains of expertise. In addition to the design of complex hardware, System-on-Chip (SoC) design requires software devel- ment, operating systems and new system architectures. Future SoC designs will resemble a miniature on-chip distributed computing system combining many types of microprocessors, re-configurable fabrics, application-specific hardware and memories, all communicating via an on-chip inter-connection network. Designing good SoCs will require insight into these new types of architectures, the embedded software, and the interaction between the embedded software, the SoC architecture, and the applications for which the SoC is designed. This book collects contributions from the Embedded Software Forum of the Design, Automation and Test in Europe Conference (DATE 03) that took place in March 2003 in Munich, Germany. The success of the Embedded Software Forum at DATE reflects the increasing importance of embedded software in the design of a System-on-Chip. Embedded Software for SoC covers all software related aspects of SoC design Embedded and application-domain specific operating systems, interplay between application, operating system, and architecture. System architecture for future SoC, application-specific architectures based on embedded processors and requiring sophisticated hardware/software interfaces. Compilers and interplay between compilers and architectures. Embedded software for applications in the domains of automotive, avionics, multimedia, telecom, networking, . .